DIFFERENT LED LIGHT EFFECT ON GONAD MATURATION AND GENE EXPRESSION IN FEMALE SYNODONTIS BROODSTOCKS (Synodontis sp.) - Sinansari, Shofihar; Sudrajat, Agus Oman; Arfah, Harton; Alimuddin, Alimuddin; Kusrini, Eni; Carman, Odang (Agency for Marine and Fisheries Extension and Human Resources, 2024)
The study investigated the influence of the different LED light spectrums on the maturation of the gonads in female synodontis broodstock and examined the maturation-related gene expression levels. Female synodontis were exposed to four different LED light spectra, specifically: white, blue, green, and red, for a continuous period of 120 days rearing. This study employed a completely randomized design, consisting of four treatments and five individual fish as replication for each treatment. An analysis was conducted on the gonadosomatic index (GSI), hepatosomatic index (HSI), gonad histology, estradiol levels, kiss2 and gnrh2 mRNA expression levels. The utilization of blue LED light treatment is highly effective in enhancing the reproductive parameters in female synodontis fish. The results show that brain and gonad kiss2 mRNA expression levels are not significantly different (P<0.05), while gnrh2 mRNA expression levels were significantly different (P<0.05) and had the highest expression in the gonads. The results suggest that light exposure can induce changes in the expression levels of kiss2 and gnrh2 mRNA, as well as control reproduction.